Terrorism, tourism and FDI: Estimating a lower bound on the peace dividend in Northern Ireland - Muckley, Cal (Statistical and Social Inquiry Society of Ireland, 2011)
In this article we estimate the economic cost of terrorism with regard to foreign direct investment and tourism in Northern Ireland during periods extending from 1970 through to 2007. Previous studies which have estimated the economic cost of terrorism internationally have neglected Northern Ireland. As a result, we focus exclusively on the economic cost of terrorism in Northern Ireland, which has been significant. In particular, our analyses indicate that for those initiatives reliant on foreign direct investment as well as for the tourism sector, a fatality as a result of terrorism imputes a minimum economic cost of #3.69 million pounds sterling. Taken together, our findings indicate an economic lower bound on the cost of terrorism in Northern Ireland.
read before the Society, 24 March 2011
Keywords: terrorism; tourism; foreign direct investment; transfer function models; 314.15